Grain Growth during Mechanical Processing of Austenitic Stainless Steel AISI 321 - Liudmila V. Radionova; Danil V. Perevozchikov; Aleksandr N. Makoveckii; Victor N. Eremin; Alexander M. Akhmedyanov; Sergey V. Rushchits (Metals, 2023)
The kinetics of austenite grain growth during thermomechanical treatment of AISI 321 steel with a relatively high content of carbon (0.07 wt. %) and titanium (0.50 wt. %) were studied. Hot deformation was carried out by the uniaxial compression of cylindrical specimens on a Gleeble 3800 thermomechanical simulator. A dependence is obtained for calculating the kinetics of austenite grain growth for a temperature range of 1150–1250 °C. The proposed dependence makes it possible to evaluate grain growth under non-isothermal conditions. The verification of the adequacy of the proposed dependence and the method for calculating the grain size at cooling rates 0.2, 1 and 5 °C/s showed its high convergence. The difference between the calculated and experimental grain size did not exceed 8%. The suppression of grain growth is due to the precipitation of titanium carbides and carbonitrides. Using the developed grain growth model, an analysis was made of the reasons for the formation of large grains in the shell after the elongating in the production process.